CONSIDERATIONS ON TEMPERATURE AND HEAT TRANSFER IN DENTAL IMPLANTS:AN EX VIVO STUDY - Razvan Curca; Cosmin - Ionuț Cretu; Andreea Tibeica; Ovidiu Stamatin; Cosmin Oniciuc; Eduard Adam; Corina Budau; Maria Camilar; Maria Bolat; Iodan Alexandru Radu; Doriana Agop-Forna; Andreea Didilescu; et al. (Romanian Journal of Oral Rehabilitation)
Teeth that have been replaced have significantly different thermal behavior than natural teeth due to the exceptional heat conductivity of the metals used for restorations, such as titanium or titanium alloy. Aim of the study: The current ex vivo investigation sets out to quantify temperature shifts in implant. We postulated that titanium dental implants could attain dangerously high temperatures due to heat conduction and the subsequent transmission of heat to the surrounding bone. Material And Method: Building a three-dimensional model was an integral part of the study with the help of Catia V5R19 program. We generated an assembly bone-implant-PMMA crown with all component elements of the complex exhibiting linear elasticity and isotropic properties of the same quality. We also conducted FEM analyses for the entire assembly, considering a range of values for temperature to which the whole complex was exposed. Results: As temperatures rise, the thermal flux affects the implant and the PMMA crown, with thermal deformations caused by expansion appearing as a result.Conclusions: When assessing the efficacy of metal dental implants, thermal stress must be considered.